Aplysina chiriquiensis, a new pedunculate sponge from the Gulf of Chiriqui, Panama, Eastern Pacific (Aplysinidae, Verongida) - Diaz, M. C.; van Soest, R. W.m.; Rützler, K.; Guzman, H. M. (Zootaxa, 2005)
A new pedunculate aplysinid sponge, Aplysina chiriquiensis, is described from shallow waters (1.5–35 m) in the Gulf of Chiriquí, western Panamá, Eastern Pacific. The species chiriquiensis is a common component of coral reefs and soft coral reefs in that region. After examining the systematic status of related taxa we conclude that there are only two valid taxa of stalked Aplysina, A. bathyphila Maldonado and Young from the Caribbean, and our new species from the eastern Pacific. A. chiriquiens is a yellow to purplish, stalked and branching sponge with oscules arranged in one or more rows along the branches. The branches can be cylindrical with smooth tapering ends, or stubby and laterally compressed. A. chiriquiensis is the first Aplysina species described from Panamá, and its distribution elsewhere in tropical and subtropical Eastern Pacific has yet to be evaluated.